Optimizing The Mawah Concept for The Economy of The Aceh Community - Mukhtasar Mukhtasar; Angga Syahputra (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2020)
Islam and Aceh are inseparable like two sides of a coin. The Serambi Makkah Country in the daily activities of its people is closely related to islamic sharia, including muamalah activities. Long before the existence of Islamic financial institutions in Indonesia, the people of Aceh had implemented cooperation in the field of muamalah as well as the mudharabah concept in Islamic financial institutions, known as mawah. Mawah is a concept of cooperation between capital owners and managers with a profit-sharing system. But the concept of mawah is still limited to cooperation in agriculture and animal husbandry, so it is necessary to development efforts in other spheres to be able to sustain the economy of the people of Aceh, as Denmark successfully developed this concept. This study uses qualitative methods by researching natural object conditions and is supported by a literature review. The results of the study revealed the need for government intervention in developing this concept in order to be optimal in developing the economy of the people of Aceh.